2014
DOI: 10.1161/strokeaha.113.003266
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Deprivation and Survival After Stroke

Abstract: In brief, the SLSR is an ongoing prospective populationbased stroke register set up in January 1995, recording all first-ever strokes in patients of all ages living in 22 electoral wards in Lambeth and Southwark (total population at the 2001 census were 271 817), inner city South London. 10,13 Stroke case ascertainment and data collection have been described in detail elsewhere. 10,14 Data collected between 1995 and 2011 were used in this analysis.Background and Purpose-Previous findings of the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…[6][7][8] The possible mechanisms of SED increasing mortality could be through poorer quality of healthcare provision, apart from patient's higher risk-factor prevalence and severity of stroke. 11,30 The current study showed that patients with SED received poorer quality of some aspects of acute and secondary preventive care of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The possible mechanisms of SED increasing mortality could be through poorer quality of healthcare provision, apart from patient's higher risk-factor prevalence and severity of stroke. 11,30 The current study showed that patients with SED received poorer quality of some aspects of acute and secondary preventive care of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, on the contrary, new data from the population-based South London Stroke Register (n=4398) found no significant difference in long-term survival (up to 17-year follow-up) associated with SES (see figure 4), except in the subgroup of black African and black Caribbean people, and differences associated with ethnic group were not significant once quality indicators of the of acute stroke care were adjusted for. 38 In summary, there is high-quality evidence that low SES is generally associated with increased risk of inhospital/short-term mortality but with some inconsistent evidence from contries with universal health care system such as Canda and UK showing no association. The relationship between SES and long-term survival is inconclusive and more high-quality studies on this are needed.…”
Section: Ses and Long-term Mortalitymentioning
confidence: 99%
“…10 The SLSR methodology has been fully described before. 10,11 In brief, the SLSR is an ongoing prospective populationbased stroke register set up in January 1995, recording all first-ever strokes in patients of all ages living in 22 electoral wards in Lambeth and Southwark (total population at the 2011 census were 357 308) in South London. Stroke case ascertainment and data collection have been described in detail elsewhere.…”
Section: Data Collectionmentioning
confidence: 99%
“…Stroke case ascertainment and data collection have been described in detail elsewhere. 10,11 Data collected between January 1995 and December 2011 were used in this analysis. …”
mentioning
confidence: 99%